PEMBIAKAN TABANUS RUMDUS (DIPTERA : TABANIDAE) DI LABORATORIUM - HARTINI, SRI; AZIZ, JANITA (BERITA BIOLOGI, 1986)
SRI HARTINI & JAMTA AZIZ. 1986. Rearing Tabanus rubidus (Diptera : Tabanidae) in the laboratory. Berita Biologi 3 (6) : 273 - 276. Horseflies Tabanus rubidus were reared in the laboratory under 27.5-°C room temperature. Flies from the field layed eggs 5.8 days (i-7 days) and hatching leaching 62.3%.The aquatic larvae required "I i as sheltei plant Two 15 monthsweie needed before larvae could be transfeired to a sintable substrate for pupation. An average of 13.5 days (18-40 days) was required for pupation The total period required to develop from eeg to imago was 109 da\s 92 114 da\s) (sexual ratio between males and females was 1.2 : 1).The first generation of flies obtained could only survue for 9.4 days (5 - 12 days) without ansisn at being abls to produce offspring. Rearing techni ques for each developmental stadia are discussed